Pengaruh Digital Marketing terhadap Penjualan UMKM Kerupuk Tempe Tiga Bintang di Desa Tanjung Mulia - Rahma Aulia Hasanah; Soviani Soviani; Nurbaiti Nurbaiti (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of digital marketing on sales growth at the small and medium enterprise (UMKM) Kerupuk Tempe Tiga Bintang in Tanjung Mulia Village. In the midst of rapid technological development, digital marketing has become an important tool for SMEs to expand their market reach and enhance competitiveness. This research employs a qualitative descriptive approach with data collected through interviews, observations, and documentation. The data were analyzed in depth to describe how the use of digital media contributes to sales activities. The findings indicate that the implementation of digital marketing through social media platforms such as WhatsApp, Facebook, and Instagram has a positive impact on increasing sales and brand awareness. Moreover, digital promotion strategies facilitate communication between business owners and consumers, strengthening customer relationships and trust. Therefore, it can be concluded that digital marketing plays a vital role in supporting the growth and sustainability of Kerupuk Tempe Tiga Bintang UMKM in Tanjung Mulia Village.